Implementasi Ijin Edar Produk Pirt Melalui Model Pengembangan Sistem Keamanan Pangan Terpadu - Bambang Hermanu; Saryana Saryana (Bangun Rekaprima, 2016)
This study examines the problems of effective implementation of the distribution permits of products PIRT as the embodiment of the system of integrated food safety still need to be developed in the form of models, in order to further refine the policy towards the level of optimization and effectiveness is expected, among other things reflected in the indicators of the realization of improved standards of food safety according to Law No. 18 Year 2012 on Food. Based on the results of previous studies have shown, that in general SKPT experienced weakness in its implementation synergy between networks are formed, and significantly tend to influence the level of effectiveness. The research method used is the juridical sociological research, in order to see the empirical facts that occurred in the community by making observations in the form of in-depth interactive communication with the relevant stakeholders as well as the producers and consumers PIRT, through the adoption of the draft approach SKPT development model has been formulated. From the results of this further research, at least can be provided alternative solutions in order to build an integrated synergy to enhance the effectiveness and optimization of the implementation of the provisions of the marketing authorization of food products of domestic industry (PIRT). Thus, on the whole range of research activities, is expected to raise the level of mutual awareness of the importance of food safety, in order to further improve the quality of consumer protection circulation of food from many food products industry household unauthorized distribution.Keywords : Distribution Permits, PIRT, SKPT, Stakeholder.